2020
DOI: 10.1186/s12872-020-01510-4
|View full text |Cite
|
Sign up to set email alerts
|

The association between Matrix Metallo-proteinases-9 (MMP-9) gene family polymorphisms and risk of Coronary Artery Disease (CAD): a systematic review and meta-analysis

Abstract: Background: We performed a systematic review and meta-analysis of the Matrix metalloproteinases (MMP)-9 (C1562T), MMP-9 (R279Q), MMP-9 (P574R) and MMP-9 (R668Q) polymorphisms and risk of Coronary Artery Disease (CAD). Methods: After a systematic literature search, pooled odds ratio (OR) and their corresponding 95% confidence interval (CI) were used to evaluate the strength of the association. Results: We identified 40 studies with 11,792 cases and 8280 controls for C1562T, 7 case-control studies with 5525 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 66 publications
1
17
0
1
Order By: Relevance
“…The DDHRR_1 model consists of two hydrophobic, two ring features, and a hydrogen bond donor. Aer the alignment of hypothesis DDHRR_1 over actives (10) and inactives (7) revealed that angles and distances are significant attributes for inhibitory activity of MMP-9. Besides, a higher degree of condence in the hypothesis model DDHRR_1 was exhibited by the higher value of QSAR model stability 0.709 on a maximum scale of 1 with an SD of 0.3473, root-mean-square-error (RMSE) of 0.48, and Pearson correlation coefficient (r) of 0.9454.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The DDHRR_1 model consists of two hydrophobic, two ring features, and a hydrogen bond donor. Aer the alignment of hypothesis DDHRR_1 over actives (10) and inactives (7) revealed that angles and distances are significant attributes for inhibitory activity of MMP-9. Besides, a higher degree of condence in the hypothesis model DDHRR_1 was exhibited by the higher value of QSAR model stability 0.709 on a maximum scale of 1 with an SD of 0.3473, root-mean-square-error (RMSE) of 0.48, and Pearson correlation coefficient (r) of 0.9454.…”
Section: Resultsmentioning
confidence: 98%
“…3,4 However, this balance is lost in numerous pathological conditions, causing chronic inammation. 5 This chronic condition is responsible for abnormal tissue degradation, causing cancers, 6,7 atherosclerosis, 8 osteoarthritis, 9 cardiovascular, 10,11 lung, 12,13 neurological, 14,15 metabolic-related disorders, and delayed wound healing in diabetes. 16 Thus, nding novel inhibitors that block the elevated levels of MMP-9 could be an attractive approach in combating the pathogenesis of several diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The most consistent evidence with respect to association of MMP-9 polymorphisms and CAD is that regarding the C1562T polymorphism. In a recent meta-analysis, Hassanzadeh-Makoui et al demonstrated that MMP-9 (C1562T) polymorphism was associated with increased risk of CAD susceptibility in the overall analysis, but markedly in the Asian population [80]. The pathophysiological background of this association is the fact that this variant of MMP-9 decreases binding potential of the proteins involved in the inhibition of transcription to the DNA sequence, thus playing a role in orchestrating the transcription activity of MMP-9 [81].…”
Section: Inflammation-based Biomarkersmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) refer to a class of proteolytic enzymes that can hydrolyze extracellular matrix. [ 11 , 12 ] Based on some researches, the invasion and metastasis of cells are related to the degradation of extracellular matrix. [ 13 , 14 ] As an important member of the MMPs family, matrix metalloproteinase-2 (MMP-2) is a proteolytic enzyme based on type IV collagen and laminin, which can specifically degrade the matrix components of normal lens capsule.…”
Section: Introductionmentioning
confidence: 99%